2008
DOI: 10.1007/s10856-008-3470-x
|View full text |Cite
|
Sign up to set email alerts
|

Controlled size and morphology of EDTMP-doped hydroxyapatite nanoparticles as model for 153Samarium-EDTMP doping

Abstract: In the original article, three authors' names were mistakenly omitted. The complete list of authors and their affiliations are listed above and below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Their attention has been focused to the field of biomaterials in order to create and develop new and improved materials for tissue engineering [1][2][3]. Among these materials, hydroxyapatite (HAp) is one of the most commonly used for bone implants [4][5][6][7][8][9] or it is a drug release system [4,[10][11][12][13][14][15]. Moreover, it has been shown that it is also a good candidate for the role of adsorbent in column chromatography, in order to separate and purify nucleic acids and proteins [3,16,17].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Their attention has been focused to the field of biomaterials in order to create and develop new and improved materials for tissue engineering [1][2][3]. Among these materials, hydroxyapatite (HAp) is one of the most commonly used for bone implants [4][5][6][7][8][9] or it is a drug release system [4,[10][11][12][13][14][15]. Moreover, it has been shown that it is also a good candidate for the role of adsorbent in column chromatography, in order to separate and purify nucleic acids and proteins [3,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been shown that it is also a good candidate for the role of adsorbent in column chromatography, in order to separate and purify nucleic acids and proteins [3,16,17]. It is possible to use hydroxyapatite for a large number of applications in the biomedical field due to its remarkable properties, such as biocompatibility, bioactivity, and osteoconductivity [4,[18][19][20][21]. In live tissue, HAp is the major mineral component of human bones and teeth [4,22,23].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations